Verifikasi Metode Uji Kadar Air Terhadap Pakan Buatan - Asmariani Asmariani; Sri Fatmah Sari (Jurnal FishtecH, 2019)
The verification test method of water content in this study including precision and accuracy parameters. Precision can be seen based on repetition (repeatability) and ignorance (reproducibility). While the accuracy has done by looking at the percent recovery (PK, % recovery). In this study, the verification method analysis of the water analyzes method content in an artificial feed is carried out gravimetrically based on the SNI method. The result of this study obtained that the analysis of water quality has qualified ripitabilty, reproducibility, and accuracy because RSD analysis obtained the smaller value than 2/3 of RD Horwitz.